Online data visualization for UMP strategic plan dashboard - Zenfoong, Andy Pue (2013)
Business Intelligence (BI) system is widely applied in many fields especially the business field which is for the purpose of producing a better decision in solving the problems and get more accurate analysis results with the visualization of graphical data. UMP is now currently using the traditional information system which is unable to represent the data or information with the suitable graphs or charts. This project is developed to build a prototype dashboard system for the purpose of monitoring the performance of each department in UMP according to the strategy plan which included the UKRA (University Key Area Result) and all of the KPI (Key Performance Index) by implementing online data visualization. Rapid Application Development (RAD) is the methodology implemented to develop this system. This dashboard system is believed can be helped in producing a better decision making solution for the problem faced through the effective graphical data form and also improving the quality of UMP.